Prevention of Osteometabolic Diseases Begins in Childhood: The Relevance of Healthy Ageing - Alves Pinto da Silva, Laisa (2023)
The present study aimed to work on providing information to students from elementary schools (from 1st to 9th grades) in the region of Ribeirão Preto - SP on how to lead a healthy life. Given this, it demonstrated the effectiveness of taking measures that positively influenced overall health and how they actively operate in their aging process. After the final tabulation and analysis of the obtained data, four thousand copies of an eight-page booklet were made with didactic activitiesto reinforce learning about osteometabolic diseases and their prevention among students and were distributed in schools that agreed to participate in the research. The study has aimed at the benefits of guidance on a healthy lifestyle, which can be composed of diversified healthy food intake, regular physical exercise, and daily doses of exposure to sunlight to obtain vitamin D throughout the week. We showed the students that putting the given guidelines into practice is important, as soonas possible, a routine that is related to the overall well-being of their organism, since they are in an important stage of learning and skeletal development.